The Problems Related to Potential Trademark Rights Infringement: Construction in Inclusive Legal Perspective on Unregistered Marks - Widiatmika, Rai; Gorda, A.A.A. Ngr. Sri Rahayu; Kurniawan, I Gede Agus; Huzaif, Syed Muhammad (Jurnal Dinamika Hukum, 2023)
In the current era of globalization and modernization, trademarks play a crucial role in distinguishing products or services in the market. Valid and protected trademark rights are valuable assets for their owners. However, the phenomenon of unregistered trademarks often poses a challenge in trademark protection. This research aims to analyze the legal construction of unregistered trademarks and the conflicts that arise from the perspective of inclusive law. The focus of this research is on the analysis of legal aspects, rights of trademark owners, consumer rights, public policies, and socio-economic aspects. The research method used is normative legal research with a dogmatic legal approach. Data sources include laws, regulations, court decisions, and legal literature related to trademarks. Data analysis techniques use a deductive approach with the application of relevant theoretical frameworks. The results of the research indicate that the inclusive legal construction in the Trademark Law provides broader protection for unregistered trademarks. Owners of unregistered trademarks can obtain protection if consistent use of the trademark in trade can be demonstrated. The inclusive approach in trademark supervision also encompasses unregistered trademarks that have potential rights to protection. Conflicts between protection of unregistered trademarks, consumer rights, and indigenous communities can be resolved through consultation and participation of relevant parties. Specific regulations that acknowledge the traditional knowledge of indigenous communities and the responsibilities of producers can also help resolve these conflicts. Mediation and arbitration mechanisms can also be used as alternative dispute resolution methods.